The Business of Hope - Raddon, Mary-Beth (Springer Nature, 2023)
This open access book contributes to research on the ascendance of neoliberalism in Canada through the vantage point of professional fundraising in the 1990s and 2000s. Fifty high-ranking fundraisers from across Canada were interviewed through 2008 and 2009 about changes they had witnessed since starting their careers. Fundraising as an occupation was burgeoning in this period in response to the devolution of state responsibility across the major domains of nonprofit activity: education, health care, social services, the arts, recreation, overseas humanitarian activities, and environmental protection. Welfare state retrenchment left the nonprofit and voluntary sector competing for private sources of funding with the help of these newly hired expert staff. As fundraisers worked to instill a culture of philanthropy, while targeting the ultra-rich and advocating for tax-favourable treatment of major gifts, they became both products and promoters of the neoliberal political and cultural reconstruction of Canadian society. This is an open access book.